ТЕМУРИЙЛАР ДАВРИ МАНБАЛАРИДА МУҲАММАД ТАРАҒАЙ АНТРОПОНИМИНИНГ ҚЎЛЛАНИШИ ВА СЕМАНТИК ХУСУСИЯТЛАРИ - Жабборов, Х. (SCIENCE and SOCIETY, 2020)
The article deals with the research of history of Temurid’s period the usage of Conqueror father’s name, semantic features and various forms of the name Taking into account histovical and linguistic sources, the author of the article proves that the Conqueror father’s name wasn’t Turgay or Taragay but Muhammad Turagay.